Demographic Differences and Customer Satisfaction towards Banking Services in Benin City, Nigeria (Journal of Entrepreneurship and Business, 2022)
This study empirically examined whether there are any significant differences on demographic and customer satisfaction towards banking services in Benin City, Nigeria. The research design employed in this study is the cross-sectional survey methodology. Three hundred and sixty seven (367); (91.75%) copies of questionnaire were returned, vividly filled and found suitable were imputed for the final data analyses. Independent samples t-Test and one-way Analysis of Variance (ANOVA) F-Test were utilized to test the hypotheses. The study found out that gender, age and occupation have positive relationships and significant differences, while marital status has an inverse relationship, but significant difference, in conclusion occupation has a positive relationship, though insignificant difference. The study recommends that regulatory and supervisory authorities should formulate and implement appropriate policies, in addition staff training and development in up-skilling and re-skilling should be boosted consistently and to conclude, demographic attributes should be considered as significant factors when delivering banking services to customers.
Keywords: Array; Array; Array; Array; Array; Array